Percutaneous closure of left atrial appendage affects mid-term release of MR-proANP - Behnes, Michael; Sartorius, Benjamin; Wenke, Annika; Lang, Siegfried; Hoffmann, Ursula; Fastner, Christian; Borggrefe, Martin; Akın, Ibrahim (Scientific reports, 2017)
The left atrial appendage (LAA) represents both a predisposing source of thrombus formation and of neuro-humoral haemostasis. This study aims to evaluate changes of biomarker expression before and after successful percutaneous closure of the LAA. Patients with atrial fibrillation and contraindication for oral anticoagulant therapy were enrolled. Blood samples were taken within 24 hours before (T1) and at least 6 months (mid-term) (T2) after successful implantation of LAA occlusion devices. Blood levels of high sensitivity troponin I and T (hsTnI, hsTnT), aminoterminal pro-brain natriuretic peptide (NT-proBNP) and mid-regional pro-atrial natriuretic peptide (MR-proANP) were evaluated at both time points. A total of 42 patients with successful percutaneous LAA closure were included. Median mid-term follow-up was of 183 days. HsTnT, hsTnI and NT-proBNP did not show any significant differences over time. Serum levels of MR-proANP increased significantly between immediate pre-intervention (T1: median = 245.7 pmol/l, IQR 155.8-361.3 pmol/l) and at mid-term follow-up (T2: median = 254 pmol/l, IQR 183.4-396.4 pmol/l) (p = 0.037). These results indicate, that percutaneous LAA closure affects neuro-humoral haemostasis by increasing MR-proANP serum levels at mid-term follow-up.